Building Quranic Literacy and Recitation Skills Through Tilawah Bil Murottal in Bengkulu Community of Sulit Air - Armin Tedy; Falahun Ni'am; Tahir Tahir; Muhlizar Muhlizar (AL Maktabah, 2026)
Quranic literacy is an essential component of Islamic education that includes the ability to read, understand, and recite the Quran correctly according to the rules of tajwid. However, many communities, particularly those experiencing socio-economic and environmental challenges, still face limitations in accessing effective Quranic learning. This article examines the implementation of the Tilawah Bil Murottal method in improving Quranic literacy and recitation skills among communities in Bengkulu. Tilawah Bil Murottal emphasizes slow, rhythmic, and accurate recitation, enabling learners to improve pronunciation, fluency, and comprehension through listening and imitation. Using a community-based learning approach, the program provides guided assistance, structured learning activities, and collective participation that foster both educational and spiritual development. The findings indicate that the implementation of Tilawah Bil Murottal contributes positively to enhancing Quranic reading abilities, strengthening tajwid application, and encouraging community engagement in religious learning. Furthermore, the program promotes social solidarity and spiritual resilience within the community. Therefore, Tilawah Bil Murottal can serve as an effective and sustainable approach to supporting Quranic literacy development in communities facing educational and social challenges.